The socio-ecological impacts of tourism development in the Western Ghats: the case of Wayanad, India - Varghese, Philip; Natori, Yoji (Frontiers in Sustainable Tourism, 2024)
Globally, tourism is advocated as a development tool with the potential to uplift socioeconomic conditions for marginalized populations and contribute to biodiversity conservation. The expectation is that the tourism model of development can bring about positive social changes in diverse communities by broadening livelihood opportunities and concurrently preserving crucial ecosystems, which are regarded as valuable assets in the tourism sector. We investigated Wayanad in the Western Ghats of India, challenging the notion of “tourism for development.” We examined the socio-ecological features of the region, the evolution of tourism and sustainable tourism, and the implications across various sectors. The research employed an empirical approach grounded in the critical examination of socio-ecological systems for tourism governance and sustainability. The data were obtained through in-depth interviews conducted in Wayanad and a review of the relevant literature. The results reveal that despite the prevalent and persuasive arguments favoring tourism, there are extensive multi-sectoral implications in tourism development that negatively affect both the environment and people at large. These impacts include the erosion of agrobiodiversity-linked traditional Adivasi lifestyles, the displacement of local communities, the encroachment of tourism projects into forests and increased human–animal conflicts, the absence of social security measures for marginalized communities, a decline in traditional livelihood options, and an overreliance on the tourism industry and the private sector. These discernible impacts have pushed the fragile region further into a socio-ecological imbalance. Tourism development in ecologically delicate areas should take into account socio-ecological impacts because a region's culture and nature are key components of its attractiveness as a tourist destination. Large-scale landscape planning should involve the perspectives of various stakeholders, including both direct and indirect participants who could be influenced by tourism. The marginalization of Adivasi communities that maintain the region's ecological integrity is unproductive for both the economic and regional development interests of tourism.